Gut microbiota and metabolic dysregulation in polycystic ovary syndrome: effects of acupuncture as an adjunct to in vitro fertilization on gut dysbiosis, metabolism, and oocyte quality - Liu, Jia-jia; Yang, Han; Xiao, Zhi-yong; Xie, Jie-hui; Su, Lan; Li, Yi-ting; Zheng, Xiao-yan; Hu, Wen-hui; Fu, Si-jia; Li, Chao-liang; Huang, Lei; Yu, Si-yi; et al. (Frontiers in Microbiology, 2026)
IntroductionPolycystic ovary syndrome (PCOS) is marked by disruptions in metabolic and reproductive endocrine functions. This study synthesizes systemic metabolic profiles, alterations in gut microbiota, and follicular fluid metabolism to elucidate the reproductive and endocrine metabolic changes associated with PCOS. Furthermore, it aims to elucidate the potential mechanisms through which acupuncture may exert therapeutic effects.MethodsIn this open-label randomized controlled trial conducted in China (November 2021–January 2023), 60 women with PCOS scheduled for In Vitro Fertilization (IVF) were randomized to receive acupuncture combined with IVF treatment or IVF treatment alone, with 30 healthy women serving as controls. Gut microbiota was sequenced and analyzed by 16S rRNA and metagenomics; follicular fluid metabolites were determined by untargeted metabolomics.ResultsCompared with healthy controls, PCOS exhibited gut microbiota dysbiosis and metabolic disorders. The specific gut microbiota in PCOS dominated by s_Lachnospiraceae, s_Blautia_sp. and g_Escherichia-Shigella, which correlated with body mass index (BMI), waist circumference, waist-to-hip ratio, and hormone levels. Acupuncture combined with IVF significantly regulated glucose and lipid metabolism, reduced g_Escherichia-Shigell abundance, and showed potential advantages in enhancing oocyte quality and embryonic developmental potential (p = 0.011). Analysis of the correlation between differential metabolites and oocyte and embryo quality demonstrated that methionine sulfoxide and boldione may be key metabolites to affect follicle quality.ConclusionPCOS is associated with systemic multi-pathway metabolic dysregulation and gut microbiota dysbiosis. It described the potential therapeutic benefits of acupuncture combined with IVF for PCOS, laying a foundation for further understanding the disease and the mechanisms of acupuncture for PCOS metabolic disorders, and providing directions for future research.